Reduced‐intensity conditioning allogeneic transplant with dual T‐cell depletion in myelofibrosis. (30th September 2019) - Salas, Maria Queralt; Lam, Wilson; Law, Arjun Datt; Kim, Dennis (Dong Hwan); Michelis, Fotios V.; Loach, David; Al‐Shaibani, Zeyad; Lipton, Jeffrey Howard; Kumar, Rajat; Mattsson, Jonas; Viswabandya, Auro
Abstract: Background: There remains a significant mortality in recipients with MF who undergo allogeneic stem cell transplant (allo‐HSCT). The combination of antithymocyte globulin (ATG) and post‐transplant cyclophosphamide (PTCy) provides good control of graft‐versus‐host disease (GVHD) when peripheral blood stem cell grafts are used. Methods: We report the outcome of 37 recipients with myelofibrosis who underwent reduced‐intensity conditioning (RIC) allo‐HSCT with ATG and PTCy. Median follow‐up was 16.4 months. Results: Nine (24.3%) recipients received 10/10 MRD grafts, 17 (45.9%) 10/10 MUD grafts, 4 (10.8%) 9/10 MUD grafts, and 7 (18.9%) haploidentical donor grafts. Six (16.3%) patients had graft failure. The cumulative incidence of grade II‐IV and grade III‐IV aGVHD at day +100 and moderate/severe chronic GVHD at 1 year was as follows: 13.5%, 5.4%, and 17%. There were no deaths secondary to GVHD. One‐year overall survival (OS), relapse‐free survival (RFS), non‐relapse mortality (NRM), and GVHD‐free/RFS (GRFS) were respectively 74.4%, 71.3%, 23%, and 43.3%. Those recipients who had worse KPS ≤ 80% had worse OS and RFS. Conclusion: RIC allo‐HSCT with ATG and PTCy results in high OS and RFS in patients with myelofibrosis and absence of mortality secondary to GVHD. Further investigations are required to reduce NRM and graft failure rates.